ANXIETY AT THE TIME OF LEARNING: HOW TO MANAGE RISKS IN LEARNING MATHEMATICS? Muhammad Ichsan Abda - Abda, Muhammad Ichsan (Samudra Publisher, 2023)
Teachers understand that learning maths is often seen as less desirable, feared and avoided by most students. Teachers use different ways of learning mathematics, both using mathematics learning and mathematics learning methods, so that students do not feel afraid and know how to master mathematical concepts. The purpose of this study is to examine and investigate the application of risk management in mathematics learning due to learning anxiety. The method used in this article is the Systematic Literature Review (SLR) method, which identifies, reviews, evaluates and interprets all existing research. Data collection was carried out by searching and reviewing 22 articles sourced from Google Scholar using Publish of Perish (PoP) software. Based on the results of this study, there are 5 important things that must be done in risk management in mathematics learning, namely (1) paying attention to the learning process which includes cognitive, affective and psychomotor aspects. (2) Always pay attention to student motivation by parents, the committee and the environment. (3) Always make mistakes to explore students' potential. (4) provide opportunities for students to choose their skills; and (5) maintain a learning environment that supports the growth of student confidence.